Identification of potential proteins involved in angiogenesis associated with cervical cancer using proteomics and bioinformatics approaches - Valero, Victoria (2021)
Angiogenesis is the growth of blood vessels from the existing vasculature and is essential in the progression of cervical cancer (CC), the fourth most common tumor in women worldwide. This process studies in search of potential biomarkers and therapeutic targets since the endothelial cells that form the abnormal tumor vasculature are characterized by changes at the protein level when are regulated by tumor and microenvironmental factors. The objective of this work was to identify potential proteins involved in the response of endothelial cells to soluble factors released by tumor cells derived from CC, using proteomics and bioinformatics approaches. We previously observed that treatment with conditioned media from CC HeLa cells (TCMs) for 24 h increases the number of endothelial HMEC-1 cells. In this work, the proteome response of HMEC-1 cells was studied underthese experimental conditions, performing a Label-Free quantitative (LFQ) mass spectrometry (MS) at the CEQUIBIEM Proteomics Center. Proteins were identified and quantified with the Proteome Discoverer software and the Uniprot database. Also, a more in-depth statistical study was performed using the Perseus software. Proteomic analysis revealed 26 proteins with increased expression levels in endothelial cells treated with TCM (P ≤ 0.05). Then, to evaluate the biological characteristics of these proteins, they were classified using the PANTHER analysis tool, according to their molecular function and biological processes. As a result of this study, catalytic activity was the most represented molecular function (11/26), followed by binding (4/26). Respect to biological processes, proteins were mainly classified into cellular processes (12/26) and energy metabolism(11/26). This analysis suggests that factors released by tumor cells mainly increase the expression of proteins involved in metabolic processes in endothelial cells. Within these proteins, the probable ATP-dependent RNA helicase DDX47 showed the greatest magnitude of change (> 2). DDX47is related to rRNA processing and ribosome biogenesis, which are processes associated with cell proliferation and cancer progression. Furthermore, ribosomal activity is also a critical regulator of metabolism. These results highlight the use of Label-Free spectrometry and bioinformatics approaches in an initial phase of discovery of potential proteins involved in cancer and suggest the potential role of DDX47 in angiogenesis associated with CC.